Analysis of Road Preservation on the Parung-Bogor Road Traffic Flow - Wardhani, Asri Kusuma; Ngadimo, Ngadimo; Muhtadi, Adhi (ASTONJADRO, 2025)
Continuous waterlogging on the road surface accelerates deformation due to the erosion process of the road base material and weakening of the pavement layer. At the same time, water flowing along the side of the road also has the potential to increase damage by eroding the structure of the roadside. Road preservation is an effort to maintain and repair to maintain the condition and function of the road so that it remains suitable for use, safe, and comfortable for users. The objectives of this study are: 1) to identify the existing condition of the height of the drainage channel against road damage, 2) to obtain the results of the study of the criteria needed for road preservation at the time of the study, 3) to analyze the results of the road preservation study against field conditions. The method used is a literature study and expert opinions on road preservation, using the Analytical Hierarchy Process (AHP). The results of this study are 1) the existing condition of the Parung-Salabenda highway found that the condition in the field of the drainage channel is higher than the road surface, so that when it rains the road will flood, 2) based on the study that the technology criteria have a very large influence, namely 0.665. This means that technology plays a very important role compared to economic and environmental criteria, 3) the results of the paired comparison analysis of technology criteria with the highest road preservation sub-criteria of 0.546 and the economic criteria sub-criteria of reducing road maintenance costs of 0.538 and finally the environmental criteria sub-criteria of high rainfall of 0.630. So that more intensive handling is needed to prevent further damage.